Comparative Analysis of The Opinions of Four Mazhab Ulama Regarding Bai' Istiglāl: Analisis Perbandingan Pendapat Ulama Empat Mazhab Terhadap Bai‘ Istiglāl - Nadiyah, Nadiyah; Sultan Antus Mohammad; Shidiq, Didi Ahmadi (Direktorat Pondok Pesantren Universitas Islam Indonesia, 2026)
This study examines the comparative opinions of the four major Islamic schools of thought regarding Bai‘ Istiglāl, an innovative contract combining bai‘ wafā’ and ijārah, used in contemporary Sukuk instruments to meet modern transactional needs. There is scholarly debate regarding the permissibility of bai‘ wafā’ as the basis for Bai‘ Istiglāl; some prohibit it, arguing it resembles interest-based transactions (riba) or uncertain transactions (gharar), while others permit it under the principle of necessity (ḍarūrah). This research employs a qualitative textual study by analyzing primary sources from the four schools, including Hāsyiyah Radd al-Muḥtār, Bulghah al-Sālik li Aqrab al-Masālik, and al-Mughnī li Ibn Qudāmah, along with secondary sources such as theses, dissertations, and other relevant scholarly publications. The findings indicate that differences in scholarly opinion arise due to the absence of explicit textual evidence, divergent interpretations regarding elements of riba, conditional sales, and similarities to rahn (pawning practices). Based on the principles of permissibility in mu‘āmalah, justice, and prevention of harm (maḍarat), Bai‘ Istiglāl is considered permissible if the contract meets the conditions of validity. The strongest opinion supports the permissibility of Bai‘ Istiglāl, provided that the contract is conducted separately, clearly, and free from riba, gharar, and unlawful gain, in accordance with QS. Al-Baqarah verses 275 and 188 and supported by hadith narrated by Ahmad and Abu Dawud. This practice is deemed valid under sharia principles if it ensures transparency, mutual consent, fairness, and aligns with contemporary transactional needs. [Penelitian ini membahas perbandingan pendapat ulama empat mazhab mengenai Bai‘ Istiglāl, yaitu struktur akad inovatif yang menggabungkan bai‘ wafā’ dan ijārah, yang digunakan dalam instrumen Sukuk kontemporer untuk memenuhi kebutuhan transaksi modern. Terdapat perdebatan di kalangan ulama mengenai keabsahan bai‘ wafā’ sebagai dasar akad Bai‘ Istiglāl; sebagian melarang karena dianggap menyerupai riba atau transaksi yang tidak jelas (gharar), sementara sebagian lain memperbolehkan dengan alasan kebutuhan mendesak (ḍarūrah). Penelitian ini menggunakan metode kualitatif berupa studi teks dengan menganalisis literatur primer dari kitab-kitab empat mazhab, termasuk Hāsyiyah Radd al-Muḥtār, Bulghah al-Sālik li Aqrab al-Masālik, dan al-Mughnī li Ibn Qudāmah, serta literatur sekunder seperti skripsi, tesis, disertasi, dan publikasi ilmiah relevan. Hasil penelitian menunjukkan bahwa perbedaan pendapat ulama muncul karena tidak terdapat dalil eksplisit, perbedaan interpretasi terkait unsur riba, jual beli bersyarat, dan kemiripannya dengan rahn (gadai). Berdasarkan prinsip kebolehan mu‘āmalah, keadilan, dan peniadaan maḍarat, Bai‘ Istiglāl dapat dibolehkan jika memenuhi syarat sah akad. Pendapat yang paling kuat mendukung kebolehan Bai‘ Istiglāl, dengan syarat akad dilakukan secara terpisah, jelas, dan bebas dari riba, gharar, serta pengambilan harta secara batil, sesuai QS. Al-Baqarah ayat 275 dan 188, serta didukung hadis riwayat Ahmad dan Abu Dawud. Praktik ini sah secara syariat jika memenuhi prinsip transparansi, keridaan, keadilan, dan relevan dengan kebutuhan mu‘āmalah kontemporer.]